Phased introduction of a universal childhood influenza vaccination programme in England: population-level factors predicting variation in national uptake during the first year, 2013/14. Issue 22 (21st May 2015) - Green, H.K.; Andrews, N.; Letley, L.; Sunderland, A.; White, J.; Pebody, R.
Abstract Introduction Through a phased rollout, the UK is implementing annual influenza vaccination for all healthy children aged 2–16 years old. In the first year of the programme in England in 2013/14, all 2–3 year olds were offered influenza vaccine through primary care and a primary school age programme was piloted, mainly through schools, in geographically distinct areas. Equitable delivery is a key aim of the programme; it is unclear if concerns by some religious groups over influenza vaccine content have impacted on uptake. Methods At the end of the 2013/14 season, variations in uptake for 2–3 year olds and 4–11 year olds were assessed and stratified by population-level predictors: deprivation, ethnicity, religious beliefs and rurality. GP practice or school level uptake was linearly regressed against these variables to determine potential predictors and changes in uptake, adjusting for significant factors. Results Uptake varied considerably by geographic locality for both 2–3 year olds and 4–11 year olds. Lower uptake was seen in increasingly deprived areas, with an adjusted uptake in the most deprived quintile 12% and 8% lower than the least deprived areas by age-group respectively. By ethnicity, the highest non-white population quartile had an adjusted uptake 9% and 14% lower than the lowest non-white quartile by age-group respectively. Uptake also varied according to religious beliefs, with adjusted uptake in 4–11 year olds in the highest Muslim population tertile 8% lower than the lowest Muslim population tertile. Conclusion In the first season of the childhood influenza vaccination programme, uptake was not uniform across the country, with deprivation and ethnicity both predictors of low uptake in pre-school and primary school age children, and religious beliefs also an important factor, particularly the latter group. With the continued rollout of the programme, these population-level factors should be addressed to achieve sustained successful uptake, along with assessment of contribution of individual and household-level factors.